2013
DOI: 10.1128/jb.00074-13
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Cluster Proteins and Flavodiiron Proteins Afford Protection to Desulfovibrio vulgaris upon Macrophage Infection

Abstract: bDesulfovibrio species are Gram-negative anaerobic sulfate-reducing bacteria that colonize the human gut. Recently, Desulfovibrio spp. have been implicated in gastrointestinal diseases and shown to stimulate the epithelial immune response, leading to increased production of inflammatory cytokines by macrophages. Activated macrophages are key cells of the immune system that impose nitrosative stress during phagocytosis. Hence, we have analyzed the in vitro and in vivo responses of Desulfovibrio vulgaris Hildenb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…4B). To confirm that the cells were experiencing NO stress, we examined expression of one of the hybrid cluster protein-encoding genes, hcp2, that has been shown previously to be induced by NO stress (41). We observed that the hcp2 gene was strongly induced in all three strains in the presence of GSNO (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…4B). To confirm that the cells were experiencing NO stress, we examined expression of one of the hybrid cluster protein-encoding genes, hcp2, that has been shown previously to be induced by NO stress (41). We observed that the hcp2 gene was strongly induced in all three strains in the presence of GSNO (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The NO donor S-nitrosoglutathione (GSNO) was added at 10 M to mid-log-phase cells. This concentration was previously shown to cause moderate inhibition of growth in D. vulgaris (41). Addition of GSNO did not affect nrfH transcription in the WT, the nrfR mutant, or the JW9382 strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so called hybrid cluster protein (Hcp) is found in many anaerobic or facultatively anaerobic bacteria, where it functions in response to nitrosative stress [217][218][219][220]. Hcp shares structural homology with anaerobic carbon monoxide dehydrogenases and contain two types of iron sulfur clusters; the first occurs as either a [2Fe-2S] or [4Fe-4S] cluster, while the second, socalled "hybrid cluster", is a unique cluster type, the precise form of which is dependent on the oxidation state.…”
Section: Hcpr2 and The Hybrid Cluster Protein (Hcp)mentioning
confidence: 99%
“…In other studies, HCP and rebredoxin oxygen oxidoreductases (ROO1 and ROO2) in D. vulgaris were demonstrated to play a role in NO protection and contributed to the survival of D. vulgaris during macrophage infection (Figueiredo et al 2013). …”
Section: Discussionmentioning
confidence: 91%